2019
DOI: 10.1111/1750-3841.14618
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and Removal of Buddy Off‐Flavor in Maple Syrup

Abstract: Buddy maple syrup is characterized by an unpleasant cabbage‐like flavor occurring generally toward the end of the sap harvest season. Occurrence of buddy off‐flavor leads to a decrease in syrup value and economic loss for the industry. It is therefore relevant to characterize the off‐flavor in order to apply corrective treatments. HS‐SPME combined with GC/MS was applied to analyze volatile aroma compounds in buddy maple syrup samples. Two novel volatile sulfur compounds were found in maple syrup: dimethyl disu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 27 publications
(35 reference statements)
0
15
0
Order By: Relevance
“…It has been suggested that alkyl-pyrazines, formed by heating amino acids and reducing sugars [ 16 , 17 ] are a causative agent of ‘buddy’ off-flavors in syrups [ 18 , 19 ]. Others have suggested that dimethyl disulfide (DMDS) and dimethyl trisulfide (DMTS) may also contribute to ‘buddy’ flavoring [ 20 ]. Although N’guyen et al .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been suggested that alkyl-pyrazines, formed by heating amino acids and reducing sugars [ 16 , 17 ] are a causative agent of ‘buddy’ off-flavors in syrups [ 18 , 19 ]. Others have suggested that dimethyl disulfide (DMDS) and dimethyl trisulfide (DMTS) may also contribute to ‘buddy’ flavoring [ 20 ]. Although N’guyen et al .…”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested that alkyl-pyrazines, formed by heating amino acids and reducing sugars [16,17] are a causative agent of 'buddy' off-flavors in syrups [18,19]. Others have suggested that dimethyl disulfide (DMDS) and dimethyl trisulfide (DMTS) may also contribute to 'buddy' flavoring [20]. Although N'guyen et al (2018) proposed that microbial activity plays a determining role in the development of 'buddy' syrup [6], Holgate showed that aseptically collected sap could also produce this off-flavor in late season [8].…”
Section: Introductionmentioning
confidence: 99%
“…Maple syrup prepared from sap collected late in the season could develop “buddy off‐flavor” with an unpleasant cabbage‐like flavor and an odor that decreases the maple syrup value (Camara et al., 2019), suggesting that harvesting time has an impact on maple syrup quality. The sap contains precursor compounds that might promote the increase in the buddy off‐flavor (Sabik et al., 2012), though little is known about the storage compounds responsible for the buddy off‐flavor.…”
Section: Processing Of Maple Food Productsmentioning
confidence: 99%
“…The sap contains precursor compounds that might promote the increase in the buddy off‐flavor (Sabik et al., 2012), though little is known about the storage compounds responsible for the buddy off‐flavor. The changes in amino acid composition in maple sap when leaf buds are opening after dormancy might cause such buddy off‐flavor (Camara et al., 2019; Morselli & Whalen, 1986). The buddy off‐flavor in the syrup has also been related to pyrazines induced in thermal‐treated food via Maillard reactions (Siegel, 2012; Van Den Berg et al, 2015) and suggests being influenced by changes in amino acid precursor of pyrazines.…”
Section: Processing Of Maple Food Productsmentioning
confidence: 99%
See 1 more Smart Citation